Knowledge and attitude of Malaysia's Muslim faith healers in dealing with the mentally ill - Sa'ad, RAM; Razali, ZA; Rani, MDM; Suhaila Sanip (Routledge Journals, Taylor & Francis Ltd, 2024)
Indexed by SCOPUS/WOS